A new synchronization method for distributed power system - Parlak, Koray Sener (Taylor & Francis Ltd, 2013)
A new method is suggested for the synchronization of an inverter into a distributed power system (DPS) and/or of a DPS into the main grid with load-sharing process. The method achieves synchronization of incoming units without any interruption in power flow or any phase shift. In this process, there is no communication between the inverter units, and the incoming units take over system load in proportion with their power rating. The method is tested through Matlab-Simulink simulations on a system consisting of the main grid and 2 three-phase inverters. The simulation results which are related to synchronization of an inverter to DPS and a DPS to main grid show promising results.
Keywords: Distributed power system; Load-frequency droop method; Microgrid; Synchronization at power system